Mincle and STING-Stimulating Adjuvants Elicit Robust Cellular Immunity and Drive Long-Lasting Memory Responses in a Foot-and-Mouth Disease Vaccine - Min Ja Lee; Hyundong Jo; Sung Ho Shin; Su-Mi Kim; Byounghan Kim; Hang Sub Shim; Jong-Hyeon Park (Frontiers in Immunology, 2019)
Conventional foot-and-mouth disease (FMD) vaccines exhibit several limitations, such as the slow induction of antibodies, short-term persistence of antibody titers, as well as low vaccine efficacy and safety, in pigs. Despite the importance of cellular immune response in host defense at the early stages of foot-and-mouth disease virus (FMDV) infection, most FMD vaccines focus on humoral immune response. Antibody response alone is insufficient to provide full protection against FMDV infection; cellular immunity is also required. Therefore, it is necessary to design a strategy for developing a novel FMD vaccine that induces a more potent, cellular immune response and a long-lasting humoral immune response that is also safe. Previously, we demonstrated the potential of various pattern recognition receptor (PRR) ligands and cytokines as adjuvants for the FMD vaccine. Based on these results, we investigated PRR ligands and cytokines adjuvant-mediated memory response in mice. Additionally, we also investigated cellular immune response in peripheral blood mononuclear cells (PBMCs) isolated from cattle and pigs. We further evaluated target-specific adjuvants, including Mincle, STING, TLR-7/8, and Dectin-1/2 ligand, for their role in generating ligand-mediated and long-lasting memory responses in cattle and pigs. The combination of Mincle and STING-stimulating ligands, such as trehalose-6, 6′dibehenate (TDB), and bis-(3′-5′)-cyclic dimeric guanosine monophosphate (c-di-GMP), induced high levels of antigen-specific and virus-neutralizing antibody titers at the early stages of vaccination and maintained a long-lasting immune memory response in pigs. These findings are expected to provide important clues for the development of a robust FMD vaccine that stimulates both cellular and humoral immune responses, which would elicit a long-lasting, effective immune response, and address the limitations seen in the current FMD vaccine.